4(x+3)=4(x+11)

Simple and best practice solution for 4(x+3)=4(x+11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+3)=4(x+11) equation:


Simplifying
4(x + 3) = 4(x + 11)

Reorder the terms:
4(3 + x) = 4(x + 11)
(3 * 4 + x * 4) = 4(x + 11)
(12 + 4x) = 4(x + 11)

Reorder the terms:
12 + 4x = 4(11 + x)
12 + 4x = (11 * 4 + x * 4)
12 + 4x = (44 + 4x)

Add '-4x' to each side of the equation.
12 + 4x + -4x = 44 + 4x + -4x

Combine like terms: 4x + -4x = 0
12 + 0 = 44 + 4x + -4x
12 = 44 + 4x + -4x

Combine like terms: 4x + -4x = 0
12 = 44 + 0
12 = 44

Solving
12 = 44

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -1-7j=-6j+8 | | 5(10)+2-4=p | | 15x+4y=55 | | 7x(n+2.9)= | | -9-9d=7-7d | | 28b^2c^4+30bc=2bc(14bc^3+15) | | 3b=2+b | | 1-4x=16+5-8x-4 | | 4p-9=3p | | 6v*.69231=1.46t | | 2x+20=8+4y | | 6(24-b)=174 | | 28ab^2c^3+30=2ab(14bc^3+15) | | (7x+12)-4x=(4x+63)-4x | | 16x=x^2+28 | | 10(12+x)=240 | | 2x+9=12x | | -96=-8(b+7) | | y^2-2y+1-x=0 | | 85(7+m)=1955 | | X+y=186 | | -10=-7u+3(u-2) | | 10-3f=-4f | | -(1+n)=-5n+5(1+2n) | | x^2-2xy+3x-6y=0 | | (-3w)=-10-4w | | 3x-32=-7x+5 | | 2x-8=-32 | | 5x^3+6x^2=0 | | (-5-6i)(7+8i)= | | 30u+4=10 | | b-9=4b |

Equations solver categories